The influence mechanism of micropore spatial distribution form on the methane desorption capability in selected Chinese coals - Xiaomin Liang; Liankun Zhang; Bo Yin; Hao Guo; Yuhao Chen; Junqing Guo; Bin Zhang (PLoS ONE, 2026)
This study quantitatively investigates the pore structure of coals with different degrees of metamorphism to reveal the spatial distribution forms of micropores and their influence on methane desorption efficiency. The results show that, as coal degrees of metamorphism, the development degree, specific surface area, and pore volume of micropores first decrease and then increase, while mesopores first increase and then decrease, and macropores decrease. The connectivity of macropores declines with increasing coal degrees of metamorphism. Micropores dominate the specific surface area (>96.5%), whereas macropores contribute the most to total pore volume (>45.2%). The study further demonstrates that attached micropores, primarily found in lignite, enable methane to desorb directly into connected seepage channels, resulting in the highest desorption efficiency. Networked micropore clusters, prevalent in coking coal, hinder gas diffusion due to complex pathways, leading to moderate desorption efficiency. In anthracite, isolated micropores impede methane release, producing the lowest desorption efficiency. These findings provide mechanistic insights into the relationship between micropore spatial distribution and gas transport, highlighting the novelty of linking pore topology to desorption behavior. They have significant implications for coalbed methane (CBM) extraction and coal mine safety management, providing guidance on optimizing gas recovery and mitigating geological hazards.